Community Dynamics of Fish Assemblages on Mid-Shelf and Outer-Shelf Coral Reefs in the Northwestern Gulf of Mexico - Wetmore, Lynne S.; Dance, Michael A.; Hill, Ronald L.; Rooker, Jay R. (Frontiers in Marine Science, 2020)
Offshore natural banks in the Gulf of Mexico (GOM) are unique model systems for examining the mechanisms structuring reef fish communities due to their substantial geographic isolation, and the presence of replicate experimental units of both low (mid-shelf) and high coral diversity (shelf-edge) reef habitats. Here, we examined the species assemblage structure of juvenile and adult fishes at two mid-shelf reefs (Sonnier and Stetson Bank) and two shelf-edge reefs (East and West Flower Garden Banks) in the northwestern GOM to evaluate the relative importance of habitat (i.e. coral diversity) vs. recruitment in structuring resident fish assemblages. Visual reef fish surveys (n = 400) were conducted at the four coral reefs during two seasons, spring-early summer and late summer-fall in 2009 and 2010. Two depth zones were surveyed at each reef, representing the reef crest (15-23 m depth) and upper slope (23-30 m depth) habitats. Seasonal variability in recruitment to both mid-shelf and shelf-edge reefs was observed, with higher mean juvenile density and diversity (Hʹ) observed during the late season at all reefs in 2009 and all but Stetson in 2010, supporting an early fall recruitment peak. Likewise, considerable inter-annual variability in juvenile recruitment was observed, with significantly lower juvenile density and Hʹ observed at mid-shelf reefs in 2010 relative to 2009. Species diversity was strongly linked to coral diversity, with greater reef fish diversity consistently observed at shelf-edge relative to mid-shelf reefs. Observed differences in the composition of juvenile and adult assemblages at mid-shelf reefs suggest that reef fish communities at these reefs were more strongly influenced by post-settlement processes (e.g. juvenile mortality) than shelf-edge reefs, which may be a function of several limiting factors (e.g., predation, coral diversity, water quality). Results indicate that reef fish assemblages associated with mid-shelf and shelf-edge reefs in the northwestern GOM have sufficient stabilizing mechanisms in place to facilitate recovery from anomalous recruitment events and maintain consistent resident assemblages. The strong, reef type-specific differences in assemblage composition observed throughout the study indicate that mid-shelf and shelf-edge coral reef habitats may fill different functional roles for demersal fishes in the northwestern GOM.